2022
DOI: 10.1002/fam.3081
|View full text |Cite
|
Sign up to set email alerts
|

Performance of clay masonry prisms with light weight plaster exposed to standard fire exposure

Abstract: Clay bricks are one of the most widely used materials in building construction due to their advantages, including local availability, ease of fabrication and cost‐effectiveness. Fire is one of the dangerous hazards that can cause damage the life and property. Lightweight plasters play a vital role in insulating the masonry construction during fire accident. There is only limited data and information available on the fire performance of Clay Brick Masonry (CBM) insulated with lightweight plaster. An extensive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…depending on the temperature were presented. Since clay bricks insulated with lightweight plaster showed an increased fire resistance compared to non‐insulated constructions, Kiran et al 6 tested clay brick masonries with its insulation to get a better understanding about the mechanical behaviour under standard fire conditions. The mechanical properties were found to be highly affected by the type of plastering, intensity and the duration of the heating procedure.…”
Section: Introductionmentioning
confidence: 99%
“…depending on the temperature were presented. Since clay bricks insulated with lightweight plaster showed an increased fire resistance compared to non‐insulated constructions, Kiran et al 6 tested clay brick masonries with its insulation to get a better understanding about the mechanical behaviour under standard fire conditions. The mechanical properties were found to be highly affected by the type of plastering, intensity and the duration of the heating procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Unprotected heated specimens (FA 120M and GGBFS 120M) showed a significantly more significant loss in impact energy of around 95.6% and 93.6%, respectively, compared to FA 0M and GGBFS 0M specimens. The study found that even after 120 min of heating, the CPP-protected SCC specimens containing EPA effectively resisted temperature penetration and reduced the loss in failure impact energy [39].…”
Section: Failure Impact Energy Of Scc Specimensmentioning
confidence: 96%
“…The interface between the body of a wall and a fire source also affected the performance of the system. Basic mathematical models were developed to describe the thermal and mechanical behaviour of clay brick walls rendered with various plaster mixes against a fire source [26]. In the same vein, the impact of a steel plate formwork and other components was examined when a composite concrete and steel wall was exposed to fire.…”
Section: Combined Investigation Of Thermal and Mechanical Performance...mentioning
confidence: 99%